High potential in table tennis from the perspectives of elite players and their youth trainers: an explorative quality study - Faber, I. R.; Oosterveld, F. G. J.; van den Heuvel, S.; Bustin, P. M. J.; Elferink-Gemser, M. T.; Nijhuis-Van der Sanden, M. W. G. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Many table tennis associations use talent development programs for identifying young high potential players and to support children aiming to become elite players. Selection criteria to participate in such programs are often based on performance results, coach`s judgments, physical appearance, perceptual-motor tests for speed, agility and coordination, motivation, self-efficacy and parental support. However, identifying young children with the potential to become a world class player is a challenge, since the key factors for future success remain ambiguous. An extensive determination of the nature of potential for table tennis is suggested to provide a better understanding of these success factors. Consequently, this multiple case study attempts to get a grip on what is meant by `high potential` for elite table tennis from the perspectives male elite players (world top 20) and the coaches of their formative years. Semi-structured interviews were conducted to unravel the multi-dimensional concept of `high potential`. After transcribing the interviews, open and axial coding will be carried out by three independent coders. Consecutively, all authors will be involved in a peer debriefing. Results of the qualitative analytic process, including a preliminary proposal of the concept of `high potential` in table tennis, will be presented during the congress.